Female-Owned Firms in Latin America : Characteristics, Performance, and Obstacles to Growth - Bruhn, Miriam (World Bank, Washington, DC, 2014)
This paper examines the characteristics and performance of female-owned firms in Latin America. Data from firm surveys show that female-owned firms tend to be smaller than male-owned firms in terms of employees, sales, costs, and physical capital. Female-owned firms also have lower profits than male-owned firms, but for larger firms this difference disappears after controlling for labor and capital inputs. Medium-size and large female-owned firms are as productive as male-owned firms of the same size, although micro and small female-owned firms are less productive than male-owned firms. There is no evidence that the differences between female and male-owned firms are due to differences in access to finance or regulatory burdens. However, this paper finds a negative correlation between child care and household obligations and female-owned firm size and performance.